The Relationship Between Regulatory Emotional Self-Efficacy and Core Self-Evaluation of College Students: The Mediation Effects of Suicidal Attitude - Zhao, Xiaojun; Shi, Changxiu (Frontiers in Psychology, 2018)
This study analysed the mediation effect of a suicidal attitude from regulatory emotional self-efficacy to core self-evaluation. A measurement study was conducted among 438 college students using the Regulatory Emotional Self-Efficacy Scale, the Core Self-Evaluation Scale, and the Suicide Attitude Questionnaire. Results from the plug-in process in SPSS and the bootstrap method showed that the attitude towards suicidal behaviour and the attitude towards family members of an individual who has committed suicide played a double-mediation role, from perceived self-efficacy in managing happiness to core self-evaluation. The results also showed that the attitude towards a person who committed suicide or attempted suicide played a mediation effect from perceived self-efficacy in managing curiousness to core self-evaluation. This research has great significance for improving the understanding of college students' sense of happiness and prevention for self-evaluation.